Biomechanical comparison of suspensory traction and axial traction in preoperative correction of cervical kyphosis: a finite element study - Chen, Hongyu; Wu, Tianchi; Pan, Shengfa; Zhang, Li; Zhao, Yanbin; Chen, Xin; Sun, Yu; Lu, William W.; Zhou, Feifei (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveTo compare the biomechanical characteristics of axial traction and suspensory traction in the process of preoperative correction of cervical kyphosis.MethodsAn intact three-dimensional finite element digital model of C2-T2 with cervical kyphosis was established. The head gravity and moment were applied to the finite element model to simulate the force of skull traction and the force of suspensory traction. The changes of cervical kyphotic angle, the length of cervical spinal canal and the stress distribution of each vertebral body were analyzed under two traction modes.ResultsThe kyphotic angles of the kyphotic segments were reduced by both tractions. The C2-C5 kyphotic angle was 41° before traction, and decreased to 32° and 26° after axial traction and suspensory traction, respectively. The length of C3-C7 cervical spinal canal was 61.3 mm before traction. After axial traction, the length of C3-C7 cervical spinal canal increased to 61.8 mm; after suspensory traction, it decreased to 59. 6 mm. The high stress area of each vertebral body was located in the anterior longitudinal ligament attachment area of the vertebral body during both two kinds of traction. The maximum Mises stress of C2-C7 vertebral body in suspensory traction is generally small relative to axial traction.ConclusionCompared with axial traction, suspensory traction has better kyphotic corrective effect, while reduces the length of the cervical spinal canal and the stress on the cervical vertebral body, which decreases the possibility of nerve damage and iatrogenic fracture during traction from a biomechanical point of view.